Exploring the function of SUPERMAN, and the repression of the trichome initiation pathway, during Arabidopsis flower development - Stewart, Darragh (Trinity College (Dublin, Ireland). Department of Genetics, 2017)
The notion that flowers are in essence modified leaves was hypothesized as far back as 1790. Supporting this early hypothesis, genetic analyses of floral organ identity genes in the model plant Arahidopsis thaliana showed that the combined loss of their activities leads to the conversion of floral organs into leaf-like structures. However, how these regulators act to suppress leaf development and control the formation of floral organs is currently not well understood. To address this knowledge gap, I used trichome initiation as a proxy for the leaf developmental program and investigated the genetic mechanisms that contribute to the suppression of trichome formation in flowers. To this end, I employed mainly a combination of mutant analyses and gene perturbation experiments. My work showed that the floral organ identity factors are directly linked, in several positions, into the regulatory network that controls trichome formation throughout plant development. It further revealed that the control of this key feature of leaf development is mediated by both independent and interacting pathways, which appear to act in a partially redundant manner. Thus, the repression of trichome initiation is a surprisingly complex regulatory process, suggesting that the suppression of other leaf features during flower development might be equally intricate.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2017